Speaking Anxiety in Online English Class: Causes and Effects - Sari Dewi Noviyanti (International Journal of English and Applied Linguistics (IJEAL), 2022)
This research analyzed speaking anxiety that occurred in English Classes at the Faculty of Ushuluddin and Humanities UIN Walisongo Semarang. The aim of this research is to analyze students’ speaking anxiety and its cause and effects. Research participants were students of the Faculty of Ushuluddin and Humanities UIN Walisongo who took the English Class in Academic Year 2021/2022. The total sample was 86 students out of 417 students. This study used questionnaires and interviews as a data collection method. The finding showed that most students have a high level of speaking anxiety. The interview also showed that students’ anxiety was caused by lack of vocabulary, problems with confidence, making mistakes fears and shyness.